Investigation of friction and perceived skin feel after application of suspensions of various cosmetic powders - Timm, Katja; Grunze, Michael (International journal of cosmetic science, 2012)
Synopsis: The perceived skin feel during and after application of skin care products is highly important to the consumer and therefore to cosmetic formulators. Powder particles are commonly incorporated in cosmetic formulations to improve their sensory properties. Although a large variety of cosmetic powders is available, it is presently uncertain how the particles' properties affect the perceived skin feel. Well-trained panellists usually assess the perceived skin feel; however, these tests are time-consuming and by nature subjective. To address this complexity, the authors have systematically investigated various suspensions of cosmetic powders with regard to the perceived skin feel after application. Furthermore, an in vitro friction measurement set-up was developed which features a tribological contact similar to the mechanical properties and the topography of the contact between finger tip and human skin. A correlation was found between the friction coefficients determined in vitro and the perceived skin feel after sample application (as assessed by a descriptive panel). The results indicate that cosmetic powder particles should be small with a rather irregular shape to better lubricate the tribological contact between finger tip and skin surface, which leads to a more ‘powdery’ skin feel. It is suggested to carry out further tests with different powder particles or other skin care formulations to fully understand the underlying mechanisms of skin feel improvement and to validate or even partly replace the results of panel testing.
First published: 28 June 2012
Gesehen am 20.06.2018